Blue-Enriched White Light Improves Performance but Not Subjective Alertness and Circadian Adaptation During Three Consecutive Simulated Night Shifts - Sunde, Erlend; Pedersen, Torhild; Mrdalj, Jelena; Thun, Eirunn; Grønli, Janne; Harris, Anette; Bjorvatn, Bjørn; Waage, Siri; Skene, Debra J.; Pallesen, Ståle (Frontiers in Psychology, 2020)
Use of blue-enriched light has received increasing interest regarding its activating and performance sustaining effects. However, studies assessing effects of such light during night work are few, and novel strategies for lighting using light emitting diode (LED) technology need to be researched. In a counterbalanced crossover design, we investigated the effects of a standard polychromatic blue-enriched white light (7000 K; ~ 200 lx) compared to a warm white light (2500 K), of similar photon density (~ 1.6 x 1014 photons/cm2/s), during three consecutive simulated night shifts. A total of 30 healthy participants (10 males, mean age 23.3 [SD = 2.9] years) were included in the study. Dependent variables comprised subjective alertness using the Karolinska Sleepiness Scale, a psychomotor vigilance task (PVT) and a digit symbol substitution test (DSST), all administered at five time points throughout each night shift. We also assessed dim-light melatonin onset (DLMO) before and after the night shifts, as well as participants’ opinion of the light conditions. Subjective alertness and performance on the PVT and DSST deteriorated during the night shifts, but 7000 K light was more beneficial for performance, mainly in terms of fewer errors on the PVT, at the end of the first- and second- night shift, compared to 2500 K light. Blue-enriched light only had a minor impact on PVT response times (RTs), as only the fastest 10% of the RTs were significantly improved in 7000 K compared to 2500 K light. In both 7000 K and 2500 K light the participants DLMO was delayed, with a mean of 2:34 (SE = 0:14) and 2:12 (SE = 0:14) hours, respectively, which was not significantly different between the light conditions. Both light conditions were positively rated, although participants found 7000 K to be more suitable for work yet evaluated 2500 K light as more pleasant. The data indicate minor, but beneficial, effects of 7000 K light compared to 2500 K light on performance during night work, while circadian adaptation did not differ significantly between light conditions. Field studies are needed to investigate similar light interventions, in order to develop recommendations regarding illumination for night workers.